2006
DOI: 10.1111/j.1479-828x.2006.00511.x
|View full text |Cite
|
Sign up to set email alerts
|

Placental assessment: Simple techniques to enhance best practice

Abstract: Valuable information on a pregnancy can be provided by ensuring histopathological examination of appropriate placentas with the simple introduction of placental information sheets, updated midwifery policy, education sessions and a colourful reminder poster.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…The human placenta is considered as a diary of fetal life as it shows changes of an adaptive nature to the intrauterine environment [1,2]. Therefore, pathologic examination of the placentas can often provide important clues for the pathogenesis of pregnancy complications [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The human placenta is considered as a diary of fetal life as it shows changes of an adaptive nature to the intrauterine environment [1,2]. Therefore, pathologic examination of the placentas can often provide important clues for the pathogenesis of pregnancy complications [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, pathologic examination of the placentas can often provide important clues for the pathogenesis of pregnancy complications [1,2]. Recent efforts by the Perinatal Section of the Society of Pediatric Pathology have provided useful and systematic diagnostic schema defining pathological changes of the placenta associated with different pathogenetic alterations: amniotic fluid infection, maternal vascular underperfusion, and fetal vascular obstruction [3e6].…”
Section: Introductionmentioning
confidence: 99%
“…Uniformly presented relevant medical and obstetric history provides clarity and use of a standard format for this is helpful. 1 The presented data should include maternal age, gravidity, parity, fetal losses, vascular disease, uterine abnormalities, systemic diseases such as hypertension, infections, caesarean(s), and also relevant family history regarding congenital anomalies and systemic diseases. Secondly, information on the current pregnancy should include: gestational age, medication, smoking and drug or alcohol use, bleeding or infection, abnormalities discovered at ultrasonographic examination, diseases in pregnancy such as infections, trauma or antepartum haemorrhages, pregnancy related diseases such as preeclampsia or gestational diabetes.…”
Section: Standardised Clinical Informationmentioning
confidence: 99%
“…[1][2][3] The College of American Pathologists (CAP) published guidelines in 1997 for pathological assessment of the placenta. 4 Despite this, Badawi et al found only 11.2% of placentas were examined, although according to the guidelines developed by CAP 43.3% had an indication for examination.…”
Section: Which Placentas Require Histopathological Assessment?mentioning
confidence: 99%
“…Other adverse pregnancy outcomes include growth restriction (6.4% of live births), prematurity (8% of live births) and neurodevelopmental disorders such as cerebral palsy (1.7/1000 births) . Histopathological analysis of the placenta can provide useful information following an adverse pregnancy outcome or suboptimal delivery conditions in many cases …”
mentioning
confidence: 99%